Honey flavonoids inhibit Candida albicans morphogenesis by affecting DNA behavior and mitochondrial function. (April 2014) - Canonico, Barbara; Candiracci, Manila; Citterio, Barbara; Curci, Rosa; Squarzoni, Stefano; Mazzoni, Annalisa; Papa, Stefano; Piatti, Elena
ABSTRACT: : Aim: Candida albicans is a pathogenic yeast, which forms a range of polarized and expanded cell shapes. We aimed to determine the correlation between honey extract (HFE) activity and changes in C. albicans cell cycle, morphology and subcellular organelles.Materials & methods: HFE anticandidal properties were investigated using flow cytometry and scanning electron microscopy.Results: Flow cytometry and scanning electron microscopy analyses indicated that HFE may inhibit the growth of the three phenotypes displayed by C. albicans and reduce infection by affecting membrane integrity. HFE affects hyphal transition by reducing the G0/G1 phase and increasing the G2/M phase. Conversely, yeast and pseudohyphae do not appear to be affected. Modifications of vacuolization and mitochondrial activity, during yeast–hypha transition establish the involvement of vacuole and mitochondria.Conclusion: HFE improved mitochondrial functionality and reduced the vacuolization, modifying the branching process associated with virulence. It is hypothesized that HFE induces changes in cell cycle progress, membrane integrity, mitochondrial function and biogenesis.